Insights into Newly Approved Drugs from a Medicinal Chemistry Perspective - Lima, Elys J. C.; Gomes, Renan A.; Fornari, Evelin; da Silva Emery, Flavio; Trossini, Gustavo Henrique Goulart (Mini Reviews in Medicinal Chemistry, 2021)
The development of new drugs is becoming notably harder each decade. To overcome the present pitfalls in the drug development pipeline, such as those related to potency, selectivity, or absorption, distribution, metabolism, excretion and toxicity properties, medicinal chemistry strategies need to be in continuous evolution and need to become even more multidisciplinary. In this review, we present how structure-based, ligand-based, and fragment-based drug design (SBDD, LBDD, and FBDD, respectively) and their respective techniques were used for the design and optimization of successful cases of New Molecular Entities (NMEs) approved by the Food and Drug Administration (FDA).
Keywords: Drug design